On Copies MV 99 and NBKM 1043 – Representatives of a Special Type of the Expanded Edition of the Synaxarion - Chistyakova, Marina (Slavistica Vilnensis, 2019)
This article continues a series of research papers dedicated to the handwritten pieces of Church Slavonic heritage of the Grand Duchy of Lithuania and the Kingdom of Poland. It examines two synaxaria of Ukrainian origin of the 17th–18th centuries — NBKM 1043 and MV 99. In terms of the composition of the articles and their calendar timelines, they represent a special type created on the basis of the expanded edition of the Synaxarion, which is characterized by special versions of the lives of saints, traditional readings expanded with didactic insertions, and new sermons. The most striking features testifying to the kinship of the manuscripts NBKM 1043 and MV 99 are hagiographical parts identically shortened during the first half of the ecclesiastical year, the calendar distribution of readings that was changed in a similar way, and specific versions of the lives of saints combining two texts in honor of one saint. A comparative analysis showed that these synaxaria are characterized by some innovations in structure due to subsequent independent editing of copies of this type of the expanded edition. A series of 13 readings are incorporated in the structure of NBKM 1043, taken from the 3rd (Lithuanian) edition of the Emerald, whereas the MB 99 or its predecessor was episodically verified with a copy similar by its contents to the synaxarion BN 12185 III.
Keywords: handwritten heritage of the Grand Duchy of Lithuania and the Kingdom of Poland; Church Slavonic Synaxarion; expanded edition; Emerald